2011
DOI: 10.1074/jbc.m111.253203
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Small Ubiquitin-like Modifier-interacting Motif in the Assembly and Regulation of Metal-responsive Transcription Factor 1

Abstract: Metal-responsive transcription factor 1 (MTF-1) 2 is a zinc finger protein that regulates gene expressions in response to various stresses, such as heavy metal exposure (1), oxidative stress (2), and hypoxia (3). MTF-1 genes have been identified in many species from insects to mammals, and encode proteins with high amino acid identities (4 -6). The N-terminal region of MTF-1 has six Cys 2 -His 2 -type zinc finger motifs that specifically bind to metal responsive elements (MREs) at the promoters of target genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…The new MTF-1 transcript is 2,773 nucleotides in length and encodes a 722 amino acid protein containing the Zn-finger DNA binding domain, all three transactivation domains and the highly conserved cysteine-rich motif (Supplementary Figure 1). In addition, the last exon of the zebrafish MTF-1 gene also contains the more recently characterized SUMO-interacting motif (SIM), 601 VIIIKQEE 608 , that immediately precedes the cysteine motif and is also conserved in other vertebrate species [7]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The new MTF-1 transcript is 2,773 nucleotides in length and encodes a 722 amino acid protein containing the Zn-finger DNA binding domain, all three transactivation domains and the highly conserved cysteine-rich motif (Supplementary Figure 1). In addition, the last exon of the zebrafish MTF-1 gene also contains the more recently characterized SUMO-interacting motif (SIM), 601 VIIIKQEE 608 , that immediately precedes the cysteine motif and is also conserved in other vertebrate species [7]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the C-terminal region of MTF-1 contains a cysteine-rich motif (C-X-C-X-C-X-C) believed to be conserved in vertebrates and has been shown to be necessary for full metal induction [8]. Recent studies have also identified a conserved SUMO-interacting motif ((V/I-X-(V/I)-(V/I)) that immediately precedes the cysteine-rich domain and appears to play important roles in regulating the subcellular localization and transcriptional activity of MTF-1 [7, 43]. A truncated MTF-1 homologue in zebrafish lacking the cysteine-rich motif typically found in vertebrates has previously been reported [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations